2(2y-1)+y=5(y+3)

Simple and best practice solution for 2(2y-1)+y=5(y+3) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2(2y-1)+y=5(y+3) equation:


Simplifying
2(2y + -1) + y = 5(y + 3)

Reorder the terms:
2(-1 + 2y) + y = 5(y + 3)
(-1 * 2 + 2y * 2) + y = 5(y + 3)
(-2 + 4y) + y = 5(y + 3)

Combine like terms: 4y + y = 5y
-2 + 5y = 5(y + 3)

Reorder the terms:
-2 + 5y = 5(3 + y)
-2 + 5y = (3 * 5 + y * 5)
-2 + 5y = (15 + 5y)

Add '-5y' to each side of the equation.
-2 + 5y + -5y = 15 + 5y + -5y

Combine like terms: 5y + -5y = 0
-2 + 0 = 15 + 5y + -5y
-2 = 15 + 5y + -5y

Combine like terms: 5y + -5y = 0
-2 = 15 + 0
-2 = 15

Solving
-2 = 15

Couldn't find a variable to solve for.

This equation is invalid, the left and right sides are not equal, therefore there is no solution.

See similar equations:

| -9x+5(-3x-4)=-42-2x | | 40+40*0+1= | | 2x+7(3x-4)=-2-3x | | -8x^2+24x-18= | | -16+x=450 | | 5x^2+50x=0 | | -5x+x=-16 | | 120x^2-272x+120=0 | | 5*5*5*5= | | 2t^2+2t=3 | | 10-3(-8-2)= | | 120x^2-272x+102=0 | | 10x-0.375-4x=6x | | 2+x=16-6x | | 30a=2a-8 | | 976x-x^2=213.495 | | 1/14=27/7*1/30 | | 10x-2y=5 | | -2x^2+17x-8=0 | | 6x-2y=1 | | -99=33y | | 8j-4k=4 | | 5(k-2)-6=5k-(4k-3) | | 3j+4k=23.5 | | 11f+10g=25 | | Y=150x+800 | | 22=-2+3s | | -2-19= | | 4m(4n-8)+6mn-2m= | | -39(11x)+26(24x)= | | 3r-6t=15 | | 6r-6t=6 |

Equations solver categories